2015
DOI: 10.1121/1.4927413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acoustic streaming from moderate-intensity pulsed ultrasound for enhancing biofilm mitigation effectiveness of drug-loaded liposomes

Abstract: Because biofilms have resistance to antibiotics, their control using minimum amounts of chemicals and energy becomes a critical issue particularly for resource-constrained long-term space and deep-sea explorations. This preliminary study investigates how ultrasound promoting penetration of antibiotic-loaded liposomes into alginate-based bacterial biofilms, resulting in enhanced bacterial (Ralstonia insidiosa) killing. Nano-sized liposomes are used as a delivery vehicle for the antibiotic gentamicin. Alginate-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In another work [29], the authors showed that the focused US and gentamicin-encapsulated liposomes reduced the number of viable bacteria in alginate-based Ralstonia insidiosa biofilms by approximately 72%, compared to US alone, gentamicin in solution alone (no liposomes) and gentamicin in solution with high-intensity focused US. These data show that high-intensity focused US in combination with an antibiotic strategy can kill bacteria within synthetic alginate biofilms, while non-focused US was able to increase the attachment of liposomes to the biofilm, as demonstrated by the same authors [30].…”
Section: Exogenous Stimuli-responsive Antibiotic Drug-delivery Syssupporting
confidence: 68%
“…In another work [29], the authors showed that the focused US and gentamicin-encapsulated liposomes reduced the number of viable bacteria in alginate-based Ralstonia insidiosa biofilms by approximately 72%, compared to US alone, gentamicin in solution alone (no liposomes) and gentamicin in solution with high-intensity focused US. These data show that high-intensity focused US in combination with an antibiotic strategy can kill bacteria within synthetic alginate biofilms, while non-focused US was able to increase the attachment of liposomes to the biofilm, as demonstrated by the same authors [30].…”
Section: Exogenous Stimuli-responsive Antibiotic Drug-delivery Syssupporting
confidence: 68%
“… 42 kHz, 0.30 W/cm 2 , 15 min. C. albicans In vitro 90%~100% [13] MLP18 20 μM 1.0 MHz, 0.97 W/cm 2 , 5 min E. coli MRSA In vivo (mice) ~60% ~80% [1] CNPs-ICG 1000 μg/mL 1 MHz, 1.56 W/cm 2 , 1 min Biofilm ( P. gingivalis, Prevotella intermedia ) In vitro 57.9% [61] Gentamicin (Nano-sized liposomes) 0.8 mg/mL 2.25 MHz, 4.4 W/cm 2 Ralstonia insidiosa biofilm In vitro 73% [87] Pd@Pt-T790 25 ppm 50 ppm 1.0 MHz, 0.97 W/cm 2 , 50% cycle, 8 min MRSA In vitro In vivo (mice) 1 ~ 5 >6 [73] Fe@UCNP-HMME 4.75 µg 1 W/cm 2 , 10 min 2 W/cm 2 , 10 min E. coli MRSA In vitro 60% 70% [22] UCNP@SiO 2 -RB 125 μg/mL 2 W/cm 2 , 10 min E. coli MRSA In vitro 70% 70% [23] UCNP@mSiO 2 (RB)-AgNPs 45 µg/mL 2 W/cm 2 , 10 min MRSA In vitro 5 [88] NM@Cur 50 mM 1.56 W/cm 2 , 1 min S. mutans In vitro 99.9% (~6 log) [75] Xanthene dye ...…”
Section: Mechanisms Of Sonodynamic Killing Of Microorganismmentioning
confidence: 99%
“…In experimental and simulation studies of streaming within cylindrical wells, such as those found in typical tissue culture systems, this includes the generation of cylindrical vortices around the axis of acoustic propagation [66]. Ultrasound-driven fluid streaming has been used to enhance fluid mixing in a variety of applications, including in vitro biological culture systems [67,68].…”
Section: Acoustic Mechanisms Of Ultrasound-induced Bioeffectsmentioning
confidence: 99%